BIOGAS - Gulen, Jale; Arslan, Hanife (YILDIZ TECHNICAL UNIV, 2005)
One of the most important factors of industrilization and development is energy. Demand of energy always increases parallel to technology developing and world population increasing. The countries which are not self sufficient in terms of energy production, needs environmentally clean, continuous, independent and renewable energy sources. Biogas, containing 55-65 % methane (CH4) can supply these features.
Keywords: Biogas; Anaerobic; Waste; Fertiliser; Engineering